2000
DOI: 10.1080/09712119.2000.9706292
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-Transfer from Feed into Pig Tissues

Abstract: Flachowsky, G. 2000. Vitamin E-transfer from feed into pig tissues. J. Appl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…They are beneficial micronutrients (DiMascio, Kaiser, & Sies, 1989;McDowell, 1989; and exert antioxidant effect via their ability to quench singlet oxygen and trap peroxyl radicals (Burton & Ingold, 1984). Antioxidants improve animal origin food quality in terms of colour, oxidative stability, tenderness, and storage properties (Angelo, 1992;Flachowsky, 2000;Flachowsky, Engelman, Sunder, Halle, & Sallmann, 2002). Lycopene, a member of the carotenoids, is mostly found in tomato and watermelon.…”
Section: Introductionmentioning
confidence: 98%
“…They are beneficial micronutrients (DiMascio, Kaiser, & Sies, 1989;McDowell, 1989; and exert antioxidant effect via their ability to quench singlet oxygen and trap peroxyl radicals (Burton & Ingold, 1984). Antioxidants improve animal origin food quality in terms of colour, oxidative stability, tenderness, and storage properties (Angelo, 1992;Flachowsky, 2000;Flachowsky, Engelman, Sunder, Halle, & Sallmann, 2002). Lycopene, a member of the carotenoids, is mostly found in tomato and watermelon.…”
Section: Introductionmentioning
confidence: 98%
“…Thus the excess production of free radicals, or the lack of antioxidant protection, can shift this balance in favour of oxidative stress. It is now well recognised that oxidative stress plays a major role in many degenerative pathologies [20]. Free radical formation is considered as a pathobiochemical mechanism which is involved in the initiation phase of various human diseases, including cardiovascular diseases, some forms of cancer, muscular degeneration and a variety of neurodegenerative diseases.…”
Section: Vitamin E As An Antioxidantmentioning
confidence: 99%
“…Levels as high as 1.2 g·day -1 in diets have been fed to growing-finishing pigs without showing toxic effects [15]. No signs of toxic effects have been reported in studies on rats, chicks and humans using vitamin E in the range of 1000-2000 mg·kg -1 of diet [1,5,16].…”
Section: Toxicitymentioning
confidence: 99%
“…Oxidative stability has been improved by antioxidant supplementation for foods of animal origin (Flachowsky, 2000;Flachowsky et al, 2002). Recent studies have shown that diets enriched with antioxidant substances could be used to attenuate the negative effects of environmental stress, which implies that detrimental effects of environmental stress could be partly consequent to induction of oxidative stress (Bollengier-Lee et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%